Transanal total mesorectal excision after incomplete endoscopic submucosal dissection for early-stage low rectal cancer: A small case series. (September 2022) - Miyasaka, Mamoru; Kitashiro, Shuji; Okushiba, Shunichi; Sumiyoshi, Tetsuya; Takeda, Hiroko; Hirano, Satoshi
Abstract: Endoscopic submucosal dissection (ESD) for colorectal cancer is challenging but is gradually being performed worldwide. It is less invasive than surgical resection and can be performed on lesions in which malignancy cannot be diagnosed. In low rectal cancers, changes such as scarring after ESD may make it challenging to preserve the anus when additional surgical resection is required. Transanal total mesorectal excision (TaTME) is a novel surgical technique involving transanal endoscopic manipulation. It is useful for lesions in the deep pelvis near the anus. Herein, we report six cases of TaTME after ESD for early-stage low rectal cancer that resulted in incomplete resection. As a representative case, a 77-year-old female was referred to our hospital, and colonoscopy revealed low rectal cancer. ESD was performed, and the pathological diagnosis was an invasion of the submucosal layer and microscopic lymphovascular invasion. We performed an additional laparoscopic low anterior resection with TaTME. Lymph node metastasis was observed, and the final diagnosis was pT1b, pN1a, pStage IIIa, and R0. In other cases, the anus can also be preserved, and the distal margin can be secured. TaTME enabled anal preservation without being affected by the ESD scars. It is considered useful for additional resection after ESD of low rectal cancer. Highlights: Additional resection after ESD for low rectal cancer is difficult. TaTME has become an attractive surgical approach to achieve an accurate DRM. TaTME has made it possible to secure the DRM, even after ESD for low rectal cancer.